2020
DOI: 10.3390/s20082260
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a New Spectral Disease Index to Detect Wheat Fusarium Head Blight Using Hyperspectral Imaging

Abstract: Fusarium head blight (FHB) is a major disease threatening worldwide wheat production. FHB is a short cycle disease and is highly destructive under conducive environments. To provide technical support for the rapid detection of the FHB disease, we proposed to develop a new Fusarium disease index (FDI) based on the spectral data of 374–1050 nm. This study was conducted through the analysis of reflectance spectral data of healthy and diseased wheat ears at the flowering and filling stages by hyperspectral imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…This clearly proved the merit of the RF classifier in modeling high-dimensional data because it intrinsically works with a random subset of features instead of all of the features of the model at each splitting point of an individual tree in the forest, thereby averaging away the feature variance. Numerous pathological and entomological vegetation studies have reported that SVM succeeded in modeling f VIs extracted from spectral bands [ 39 , 89 , 90 ], while at the same time the modeling performance of for the RF classifier was found to be stable and superlative with transformed spectral reflectance data [ 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…This clearly proved the merit of the RF classifier in modeling high-dimensional data because it intrinsically works with a random subset of features instead of all of the features of the model at each splitting point of an individual tree in the forest, thereby averaging away the feature variance. Numerous pathological and entomological vegetation studies have reported that SVM succeeded in modeling f VIs extracted from spectral bands [ 39 , 89 , 90 ], while at the same time the modeling performance of for the RF classifier was found to be stable and superlative with transformed spectral reflectance data [ 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al obtained a detection accuracy of 75% with SVM optimized with a genetic algorithm, using correlation analysis and wavelet transform for the selection of important bands, vegetation indices and wavelet features [24]. Zhang et al developed a new Fusarium disease index (FDI) after determining the best index from the existing indices with PLS regression, reaching 89.8 accuracy in detecting F. graminearum [129,130]. Whetton et al studied FHB in the laboratory and field in the wheat cultivar Solstice, using PLSR to determine FHB from yellow rust in wheat and barley [131,132].…”
Section: Hyperspectral Remote Sensing Of Wheat Diseasesmentioning
confidence: 99%
“…Spectral differential transform and continuum removal transform can eliminate some background effects and can increase implicit information, so differential spectral features and continuum removal spectral features are widely used in detecting crop disease spectra [26,27]. In addition, eight vegetation indices were selected and applied for use in the spectral detection of crop diseases [11,25,28]: (1) photosynthesis-physiological reflectance index (PHRI); (2) pigment variation parameters-triangular vegetation index (TVI), anthocyanin reflectance index (ARI) and normalized pigment chlorophyll index (NPCI); (3) greenness-greenness index (GI); (4) biophysical parameters-narrow band normalized vegetation index (NBNDVI) and plant senescence reflectance index (PSRI); and (5) water and nitrogen content-nitrogen reflectance index (NRI). The sources of definitions, references and descriptions of these 16 traditional SFs are summarized in Table 1.…”
Section: Traditional Spectral Featuresmentioning
confidence: 99%